UPAYA MAJELIS TAKLIM AT-TAKWA DALAM PEMBINAAN KEBERAGAMAAN MASYARAKAT PADANG ALAI KECAMATAN PANTI KABUPATEN PASAMAN - Riana Melti, Riana melti (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2023)
This research is motivated by the lack of public awareness in carrying out congregational prayers at mosques, attending Islamic studies and events held at mosques. The efforts of the At-Takwa Taklim Council can be seen from the guidance carried out by the Padang Alai taklim at-takwa council based on the aspects of faith, worship and muamalah. With these three aspects, the guidance by the Taklim Council takes the form of activities such as weekly afternoon Wirid activities at the Padang Alai Taqwa Mosque, weekly Wirid Evening at the Taqwa Padang Alai Mosque, and weekly wird yasin. This research uses qualitative methods, supported by observations and interviews, so that systematic results and implementation are found. The results of this research show that society is starting to show changes for the better, such as: starting to diligently attend the Koran, being willing to give alms and help others, not gossiping and discussing other people's problems, and starting to do good deeds that are beneficial for themselves and others. . This indicates that the presence of the Taklim assembly has had a good impact on the religious community.